Temporomandibular Joint: MR Imaging of Internal Derangements and Postoperative Changes - Schellhas, Kurt P.; Wilkes, Clyde H.; Fritts, Hollis M.; Omlie, Mark R.; Heithoff, Kenneth B.; Jahn, Jeffrey A. (American Journal of Neuroradiology, 1987)
Nineteen abnormal temporomandibular joints (TMJs) imaged with high-field-strength surface-coil MR are presented to illustrate specific changes associated with disk derangement, trauma, and previous surgery. Cases were selected from a series of 248 TMJ MR studies in 144 patients (9–68 years old, 130 females and 14 males) performed during a 5-month period. Surgical findings were available for correlation in 44 of the 248 joints studied. Increased signal caused by myxoid degeneration within the degenerating meniscus was seen, as were pathologic changes including atrophy, fibrosis, and contracture of masticatory muscles occurring with internal degrangements. Advantages and limitations of MR are discussed with reference to arthrography and videofluoroscopy. High-resolution and partial-flip-angle images of a normal joint are provided for comparison. In most clinical circumstances, MR is the procedure of choice when examining the TMJ, because it provides contrast resolution of soft-tissue structures superior to that of conventional imaging techniques.